Placental inflammation in spontaneous preterm birth and neonatal outcomes - Rooprai, Parminder Singh; Mathai, Sheila Samanta; Gupta, Divya (Indian Journal of Child Health, 2019)
Background: Preterm birth (PTB) can be classified as spontaneous or indicated. The complications of PTB can affect all systems and result in chronic physical and mental disabilities. Objective: The objective of the study was to assess the incidence of placental inflammation in PTB with and without preterm premature rupture of membranes (pPROM) and its effects on various neonatal outcomes. Materials and Methods: This prospective observational study was conducted in a tertiary hospital where all preterm neonates born by spontaneous onset vaginal delivery and cesarean section were included in the study. Neonates born to mothers having significant uterine anomalies, multiple gestations, and those with any major congenital anomalies were excluded from the study. Placentas were assessed for evidence of inflammation on histopathological examination. Correlation of placental inflammation with neonatal morbidity and mortality was also assessed. Results: The incidence of placental inflammation in spontaneous onset preterm births (sPTB) was found to be 29%. Most placentas showed Stage 1 chorioamnionitis (47%). Three placentas had evidence of fetal inflammatory response, of which one had early funisitis (Stage 1) and two had intermediate funisitis (Stage 2). Of the nine neonates who had features of sepsis (definite or probable), 4 (44.4%) had evidence of placental inflammation. No significant association was found between placental inflammation and other secondary outcomes such as duration of neonatal intensive care unit stay, neonatal mortality, requirement of phototherapy, and need for continuous positive airway pressure support. Conclusions: Placental inflammation was seen in almost one-third of cases of sPTB, of which 78% were without pPROM. Hence, sPTB irrespective of pPROM should be considered as indirect marker of ongoing inflammation.